Gambaran Mikroskopis Bakteri Neisseria gonorrhoeae Pada Pasien Gonore dan Pemantapan Mutu Internalnya di Puskesmas Gedongtengen Yogyakarta: - - Endita Widya Sari; Dhiah Novalina; Novita Eka Putri (LPPM Universitas Abdurrab, 2025)
Gonorrhea is a sexually transmitted infection with clinical symptoms of mucosal inflammation and pus formation in the genital area due to infection with the bacteria Neisseria gonorrhoeae. Transmission of gonorrhea infection can occur when the bacteria are transmitted through bodily fluids, sexual contact with sufferers, and deviant social behavior (MSM or FSW). Examination of patients diagnosed with gonorrhea requires accurate validation of results to improve internal quality, so that internal quality assurance of examinations is necessary. This study aims to determine the microscopic appearance of Neisseria gonorrhoeae bacteria in gonorrhea patients and to strengthen its internal quality assurance at the Puskesmas (Primary Health Center) Gedongtengen, Yogyakarta. The study used a descriptive study using a cross-sectional method. Data samples were taken from the medical records of patients who underwent gonorrhea examinations from January to May 2025 with a total of 35 patients, and positive results were dominated by female patients, with 8 patients. Gonorrhea examinations were carried out using the Gram staining method and then examined microscopically. The positive specimens showed clear morphology of DGNI (Gram-Negative Intracellular Diplococci) and PMN (Polymorphonuclear Cells), coffee bean-shaped, non-spore-forming, and non-motile bacteria. The entire examination process, including result validation and quality assessment, followed standard operating procedures (SOPs). The internal quality assurance assessment for gonorrhea examinations at Puskesmas Gedongtengen laboratory have met the standards with good qualifications, as stated in Puskesmas Gedongtengen SOP policy 43/UKPP/LAB/2023 concerning Internal Quality Assurance for Gonorrhea Examination.